(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Nouri Z, Zobeiri M, Feghhi J, Amiri GZ, Marvie Mohadjer MR. 2015. Comparison of woody species diversity between managed and unmanaged forests considering vertical structure in Hyrcanian forests, Iran. Biodiversitas 16: 95-101. Biodiversity conservation is increasingly considered a key to sustainable forest management and understanding biodiversity in forest ecosystems is essential to reveal forest dynamics, so this study aims to compare tree and shrub species diversity and vertical species distribution between two managed and unmanaged forest stands. The study area was consisted of two adjacent districts in which two different management practices were implemented. In 1000 m2 circular plots, type of species and diameter at breast height (D.B.H) of all trees larger than 2.5 cm as well as type of species of all shrubs and vertical distribution of tree species were recorded. In addition to richness, evenness and heterogeneity indices were calculated for whole tree and shrub species and also for each tree layer. The results showed that tree species diversity indices were significantly greater in the unmanaged area, whereas richness and heterogeneity indices of shrubs were greater in the managed area. Comparing the biodiversity indices indicated that richness index had the greatest value in the understorey and heterogeneity indices were greatest in the middle storey in both regions. Greater amounts of evenness were detected in the middle- and over storey of unmanaged and managed areas, respectively. As forestry operations result in change in various forest characteristics such as species diversity, it is essential to assess and monitor the effect of logging operations on forest diversity Hyrcanian forests of Iran.